'I want to be able to do what I know the tools will allow us to do': Practicing evaluative bibliometrics through digital infrastructure. Issue 4 (6th October 2022) - Krüger, Anne K; Petersohn, Sabrina
Abstract: The proliferation of quantitative research assessment has been accompanied by an increasing growth and diversification of digital infrastructure for evaluative bibliometrics. Since the beginning of the 2000s, insights into academic performance provided by a variety of new databases and devices significantly exceed the capacities of the former Science Citation Index and embedded metrics. Going beyond the research on the construction, uses, and consequences of bibliometric indicators, we therefore posit that a perspective on bibliometric infrastructure is crucial for understanding how evaluative bibliometrics is put into practice. Drawing on interviews with academic librarians on the increasing provision and implementation of bibliometric infrastructure in the years 2013 and 2014, we analyse how the entanglement of technology and its users shapes how evaluative bibliometrics is understood and practiced.